Cover Picture: Sulfur‐Free Radical RAFT Polymerization of Methacrylates in Homogeneous Solution: Design of exo‐Olefin Chain‐Transfer Agents (R−CH2C(=CH2)Z) (Angew. Chem. Int. Ed. 52/2022). Issue 52 (22nd November 2022) - Amano, Maki; Uchiyama, Mineto; Satoh, Kotaro; Kamigaito, Masami
Abstract : Sulfur‐free RAFT homogeneous polymerization of methacrylates was achieved by using exo ‐olefin compounds with substituted α ‐methylstyrene units and the methyl–methacrylate dimer structure, as reported by Kotaro Satoh, Masami Kamigaito, and co‐workers in their Research Article (e202212633 ). Colorless sulfur‐free multiblock copolymers were also prepared by sequential monomer additions.